2022
DOI: 10.1177/21582440221096437
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Access to Finance, Entrepreneurial Self-Efficacy, Attitude Toward Entrepreneurship, Entrepreneurial Ability, and Entrepreneurial Intentions: A Botswana Youth Perspective

Abstract: Governments in emerging markets in Africa need to focus more on the factors that drive the entrepreneurial ability of the youth on the continent. This approach is required to lower unemployment levels through self-employment and stimulating entrepreneurial intentions among graduates. Considering this, the research aimed to determine the factors influencing youth entrepreneurial ability and their effect on entrepreneurial intentions. Data were collected through a cross-sectional survey from 347 youths enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 108 publications
2
19
0
Order By: Relevance
“…This aspect emphasizes that many behaviors are not totally within volitional control, which is reflected in prior practices and the existence or lack of opportunities and resources. Research has shown that the TPB is responsible for 27% and 39% of the diversity in behavior and intentions (Svotwa et al 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect emphasizes that many behaviors are not totally within volitional control, which is reflected in prior practices and the existence or lack of opportunities and resources. Research has shown that the TPB is responsible for 27% and 39% of the diversity in behavior and intentions (Svotwa et al 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Entirely of this finally leads to the possibility of economic progress and development (Choi et al 2021;Nungsari et al 2022). There has been a significant increase in the amount of money invested in entrepreneurship education as a result of both private and public organizations across the globe realizing this potential (Svotwa et al 2022;Xiong et al 2022). It has been widely celebrated, but many in the sector are still unsure if any of this investment is worthwhile.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of students, ATE is the degree to which students desire or do not desire to engage in entrepreneurial behaviors. Many researchers have also explored the positive relationship between ATE and EI ( Jena, 2020 ; Anjum et al, 2022 ; Bakar et al, 2022 ; Svotwa et al, 2022 ). The meta-analysis of entrepreneurship literature conducted by Hazarika et al (2020) also indicates that ATE has the strongest predictive potential for EI, accounting for more than half of the total variance.…”
Section: Hypothesesmentioning
confidence: 99%
“…On the one hand, the reason for this phenomenon is that the entrepreneurial process is full of difficulties and uncertainties. A large number of data show that the failure rate of start-ups in 5 years is as high as 67% ( Svotwa et al, 2022 ). On the other hand, it is due to the lack of experience and knowledge accumulation of entrepreneurs ( Wach and Bilan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Original Research http://www.sajesbm.co.za Open Access Svotwa et al (2022) suggested in their study that youth should be educated on how to develop business plans and make use of financial information relating to business decisions.…”
Section: Determinants Of Youth Participation In Agriculturementioning
confidence: 99%